Design of a high-efficiency thin-type metasurface hologram. Issue 15 (13th October 2022) - Hao, Honggang; Ran, Xuehong; Tang, Yihao; Zheng, Sen
Abstract : To improve the imaging efficiency and reduce profile, a high efficiency, thin-type metasurface hologram based on induced magnetism is proposed. Both types of units consist of two asymmetric electric dipole elements printed on a thin-type dielectric substrate with only 1.3 mm thickness ( λ 0 /6.4 at 36 GHz). By tuning the magnetic and electric responses, the transmitting phase of the units can be changed. Both types of units are designed to cover the quantized 2π phase range with the transmittance above 90%. Based on holographic theory, the target image field distribution and the incident plane wave can be regarded as object wave and reference wave respectively. A holographic metasurface is designed to record phase information of the target image. The simulation and experiment show that the designed metasurface can reproduce a clear image with a 65.86% imaging efficiency, which provides a new way to realize high-efficiency holographic imaging.